Grain boundary diffusion material, diffusion magnet and method
By forming a specific rare earth alloy film on the surface of the sintered NdFeB magnet and performing vacuum heat treatment, the problems of limited diffusion depth and cumbersome processes in the existing technology are solved, and the coercive force of the magnet is effectively improved and the utilization of heavy rare earths is improved. , suitable for industrial production.
Patent Information
- Application Number
- CN202411551785.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-13
AI Technical Summary
The existing grain boundary diffusion technology has limitations in improving the coercive force of sintered NdFeB magnets, especially the limited diffusion depth of heavy rare earth elements caused by concentration gradients, and the existing methods are cumbersome and unfavorable to industrial production. The coercive force is Inadequate improvement.
Use rare earth alloy films containing heavy rare earth elements such as Pr, Nd, Dy and Tb to form rare earth films on the surface of sintered NdFeB magnets through film formation processes such as spraying and magnetron sputtering, and realize grain boundary diffusion in vacuum heat treatment. , optimize the ratio of Cu, Zr, Ta, Nb and other elements to improve magnet performance.
The coercive force of the magnet is significantly improved, the residual magnetic drop rate is small, and the heavy rare earth utilization rate is high, which is suitable for industrial production. The coercive force increase range is greater than or equal to 11.8kOe, the residual magnetic drop rate is less than or equal to 1.3%, and the heavy rare earth utilization rate is improve.
Smart Images

Figure BDA0005115280680000151 
Figure BDA0005115280680000152
Abstract
Description
Technical Field
[0001] The invention relates to a grain boundary diffusion material, a diffusion magnet and a method. Background Art
[0002] Generally speaking, the core of grain boundary diffusion technology is to utilize the diffusion behavior of heavy rare earth elements at the grain boundaries of magnets to improve the overall performance of magnets by forming a high coercive force shell. Specifically, a layer of heavy rare earth film is first formed on the surface of the magnet, and then heat treated under vacuum or inert gas protection. At high temperatures, heavy rare earth elements diffuse rapidly along the grain boundaries into the interior of the magnet and replace the Nd atoms around the main phase grains to form a high coercive force shell. This shell can effectively inhibit the nucleation and growth of the reverse magnetization domain, thereby improving the coercive force of the magnet.
[0003] As an effective method to improve the performance of magnets, the grain boundary diffusion technology of sintered NdFeB magnets has achieved remarkable results in industrial production, but it still faces some technical difficulties. For example, due to the existence of concentration gradients, the diffusion depth of heavy rare earth elements is limited, resulting in poor improvement in the coercive force of magnets. For another example, although the grain boundary diffusion technology can significantly reduce the use of heavy rare earth elements compared to traditional processes, how to further improve the utilization rate of heavy rare earth elements remains a challenge. This involves many aspects such as the selection of diffusion sources and the optimization of diffusion processes.
[0004] CN105529123A discloses a grain boundary diffusion material and a rare earth permanent magnet material and a preparation method thereof. The constituent elements of the grain boundary diffusion material are R L , R H , Fe, Co, M', Nb, among which R L is Pr and / or Nd; R H is at least one of Dy, Tb and Ho; M' is at least one of Al, Cu, Zn, Sn, Ag, In, Pb, Bi, Ge, Ti, V, W, Cr, Zr, Hf, Mn, Ni, Sb, Mo, Ga, Si and B. The purpose of grain boundary diffusion is to obtain higher magnet performance with less rare earth consumption. The components of this method contain alloy elements such as ferromagnetic elements Fe and Co that are not conducive to the improvement of the coercive force of grain boundary diffusion magnets. In addition, in Example 1 of this method, the magnet is 15mm long × 10mm wide × 1mm thick, while the volume of the diffusion source alloy is 35mm long × 30mm wide × 5mm thick, that is, the diffusion source is much larger than the magnet itself, which is very unreasonable. Similar situations exist in other embodiments. In addition, the improvement of the coercive force of sintered NdFeB magnets by the grain boundary diffusion material still needs to be further improved.
[0005] CN114875290A discloses a multiphase structural alloy for grain boundary diffusion and a method for preparing a high-performance NdFeB magnet. The constituent elements of the multiphase structural alloy for grain boundary diffusion are R1, R2, M1, M2 and M3, R1 includes one or more of Pr, Nd, La, Ce and Y; R2 includes one or more of Dy, Tb, Ho and Gd; M1 includes one or more of Fe, Co and Ni; M2 includes one or more of Cu, Al, Ga, Mg, In and Sn; M3 includes one or more of Ti, Zr, Nb, Mn and Cr. The diffusion source contains high content of ferromagnetic elements such as Fe, Co and Ni, and the remanence Br of the magnet after diffusion decreases seriously (such as Br decreases by 580Gs in Example 1, 650Gs in Example 2, and 720Gs in Example 3), and the comprehensive performance of the magnet needs to be improved. In addition, the method requires that the raw materials of the grain boundary diffusion source be smelted to obtain alloy ingots and then subjected to multi-stage annealing treatment, resulting in cumbersome procedures.
[0006] CN117038313A discloses a method for preparing a grain boundary diffusion source and a rare earth magnet. The constituent elements of the grain boundary diffusion source are HRE, M, La, and Ga, wherein M is selected from one or more of Fe, Co, Al, Cu, Ni, Ge, Zr, Ti, Nb, Mo, Hf, Ta, or W; and HRE is selected from one or more of Dy or Tb. The grain boundary diffusion source is more suitable for the diffusion of sintered NdFeB magnets containing Ce elements. The coercive force increment still needs to be further improved.
[0007] CN111916284A discloses a method for preparing a NdFeB magnet, comprising: before orientation pressing, using a vapor deposition method, depositing an R metal layer, an M metal layer, and an HL or HH metal layer on the NdFeB powder in sequence to form a mixed metal film layer, wherein R is at least one of Tb and Dy, M is at least one of W, Mo, Ti, Zr and Nb, H is at least one of Pr, Nd, La and Ce, and L is one of Cu, Al and Ga; after orientation pressing, vacuum sintering and aging treatment are performed to obtain the NdFeB magnet. In view of the small particle size, high activity and poor fluidity of NdFeB powder, the processing process faces high safety risks, and it is difficult to obtain a high-quality alloy layer on the surface of the magnetic powder. In addition, the equipment performance requirements are high and the processing efficiency is low. The preparation method is not conducive to industrial production, and the coercive force improvement still needs to be further improved.
[0008] CN115116734A discloses a method for improving grain boundary diffusion to prepare high-performance NdFeB permanent magnet materials, comprising the following steps: after the NdFeB magnet is pre-treated, a heavy rare earth layer is plated on the NdFeB magnet, and then a high melting point metal layer is plated to obtain a NdFeB magnet containing a composite coating; the NdFeB magnet containing a composite coating is heat-treated, and then the high melting point metal layer is removed to obtain a NdFeB permanent magnet material; the high melting point metal layer includes at least one of a tungsten layer, a zirconium layer, a molybdenum layer, a tantalum layer, and a niobium layer. The high melting point metal layer in this method is separated from the rare earth diffusion layer, and needs to be removed again after the diffusion is completed. The complex process investment does not produce a significant improvement in the magnet performance, but instead causes a waste of high melting point metal. In addition, the rare earth diffusion source layer is a separate heavy rare earth layer, which has a high melting point, poor wettability, a long diffusion high temperature insulation time, and a limited increase in the coercive force of the magnet after diffusion. Summary of the invention
[0009] In view of this, one object of the present invention is to provide a grain boundary diffusion material, which can significantly increase the coercive force of the magnet and reduce the remanence. Another object of the present invention is to provide a method for preparing a diffused magnet. Another object of the present invention is to provide a diffused magnet prepared according to the preparation method as described above.
[0010] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0011] In one aspect, the present invention provides a grain boundary diffusion material, which comprises R, M 1 and M 2 ; Wherein, R is selected from at least one of Pr, Nd, Dy and Tb, and must contain a heavy rare earth element; M 1 At least one selected from Zr, Hf, Ta and Nb; M 2 Two selected from Al, Cu, Ga and Mg, and must contain Cu;
[0012] The grain boundary diffusion material is used to form a rare earth alloy film, and the rare earth alloy film has the following composition: x M 1 y M 2 z ,in,
[0013] x is the weight fraction of R element, y is the weight fraction of M 1 The weight fraction of the element, z is M 2 The weight percentage of the element, and the content of Cu is greater than z / 2;
[0014] Based on 100 parts by weight of the rare earth alloy film, x is 60 to 75 parts by weight, y is 3.5 to 15 parts by weight, and z is 10 to 36.5 parts by weight.
[0015] According to the grain boundary diffusion material of the present invention, preferably, R must contain Dy or Tb; M 1 At least one selected from Zr, Ta and Nb.
[0016] On the other hand, the present invention also provides a rare earth alloy film having the following composition: x M 1 y M 2 z , wherein R is selected from at least one of Pr, Nd, Dy and Tb, and must contain a heavy rare earth element; M 1 At least one selected from Zr, Hf, Ta and Nb; M 2 Two selected from Al, Cu, Ga and Mg, and must contain Cu; x is the weight percentage of R element, y is the weight percentage of M 1 The weight fraction of the element, z is M 2 The weight percentage of the element, and the content of Cu is greater than z / 2;
[0017] Based on 100 parts by weight of the rare earth alloy film, x is 60 to 75 parts by weight, y is 3.5 to 15 parts by weight, and z is 10 to 36.5 parts by weight.
[0018] In another aspect, the present invention further provides a method for preparing a diffusion magnet using the grain boundary diffusion material as described above, comprising the following steps:
[0019] (1) pre-treating the surface of the sintered NdFeB magnet to remove pollutants on the surface, thereby obtaining a pre-treated sintered NdFeB magnet;
[0020] (2) forming the rare earth alloy thin film on two opposite surfaces of the pretreated sintered NdFeB magnet perpendicular to the C-axis orientation direction through a film forming process to obtain a coated magnet;
[0021] (3) subjecting the obtained coated magnet to vacuum heat treatment to obtain a diffused magnet;
[0022] Wherein, the rare earth alloy film formed on one surface of the pretreated sintered NdFeB magnet has a thickness of less than 60 μm.
[0023] According to the method of the present invention, preferably, the sintered NdFeB magnet is RE2Fe 14 The B-type compound is the main phase, in which RE is a rare earth element.
[0024] According to the method of the present invention, preferably, the pretreatment comprises the following steps: using sandblasting to remove pollutants on the surface of the sintered NdFeB magnet, and then ultrasonically cleaning with an organic solvent to obtain the pretreated sintered NdFeB magnet.
[0025] According to the method of the present invention, preferably, the film forming process is selected from one of spraying, screen printing, laser cladding, brazing, evaporation coating and magnetron sputtering.
[0026] According to the method of the present invention, preferably, the rare earth alloy film formed on one surface of the pretreated sintered NdFeB magnet has a thickness of 15 to 35 μm.
[0027] According to the method of the present invention, preferably, the vacuum heat treatment comprises the following steps:
[0028] The coated magnet is placed in a vacuum heat treatment furnace, and under the condition of a vacuum degree of less than or equal to 5Pa, the temperature is raised to 600-850°C, and kept at this temperature for 0.5-5h; then the temperature is continued to be raised to 850-950°C, and kept at this temperature for 3-8h. After the insulation is completed, it is cooled to room temperature; then the temperature is raised to 400-658°C, and kept at this temperature for 1-5h. After the insulation is completed, it is cooled to room temperature to obtain a diffused magnet.
[0029] In another aspect, the present invention further provides a diffused magnet, which is prepared according to the method described above.
[0030] The invention can improve the coercive force of the magnet to a greater extent through the specific grain boundary diffusion material, the remanence decrease rate is small, and the utilization rate of heavy rare earth is high. The preparation method of the diffusion magnet of the invention is more conducive to industrial production. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0032] The "remanent magnetism" mentioned in the present invention refers to the value of the magnetic flux density corresponding to the point where the magnetic field intensity is zero on the saturation hysteresis loop, and the unit is Tesla (T) or Gauss (Gs). 1Gs = 0.0001T.
[0033] The "coercive force" mentioned in the present invention, also known as intrinsic coercive force, refers to the magnetic field intensity when the magnetic field is monotonically reduced to zero and then increased in the opposite direction from the saturated magnetization state of the magnet, so that the magnetization intensity decreases to zero along the saturation hysteresis loop, and the unit is Oersted (Oe) or Ampere / meter (A / m). 1Oe = 79.6A / m.
[0034] <Grain boundary diffusion materials and rare earth alloy films>
[0035] The present invention provides a grain boundary diffusion material, which comprises R, M 1 and M 2 ; Wherein, R is selected from at least one of Pr, Nd, Dy and Tb, and must contain a heavy rare earth element; M 1 At least one selected from Zr, Hf, Ta and Nb; M 2 Two materials are selected from Al, Cu, Ga and Mg, and Cu must be contained. Such grain boundary diffusion materials are beneficial to further improve the coercive force of the magnet, and the utilization rate of heavy rare earth is high.
[0036] The grain boundary diffusion material of the present invention is used to form a rare earth alloy film. The rare earth alloy film can be formed on the surface of a sintered NdFeB magnet, and then the grain boundary diffusion is carried out through heat treatment to obtain a diffused magnet with a large increase in coercive force.
[0037] In the present invention, the grain boundary diffusion material can be formed into a rare earth alloy film on the surface of the sintered NdFeB magnet through a film forming process selected from the group consisting of spraying, screen printing, laser cladding, brazing, evaporation coating and magnetron sputtering.
[0038] In the present invention, R is selected from at least one of Pr, Nd, Dy and Tb, and must contain a heavy rare earth element. According to one embodiment of the present invention, R is selected from at least one of Pr, Nd, Dy and Tb, and must contain Dy. According to another embodiment of the present invention, R is selected from at least one of Pr, Nd, Dy and Tb, and must contain Tb.
[0039] In the present invention, M 1 At least one selected from Zr, Hf, Ta and Nb, preferably at least one selected from Ti, Zr, Ta and Nb. According to one embodiment of the present invention, M 1 According to another embodiment of the present invention, M 1 According to another embodiment of the present invention, M 1 According to another embodiment of the present invention, M 1 For Zr and Nb.
[0040] In the present invention, M 2 Two selected from Al, Cu, Ga and Mg, and must contain Cu. According to one embodiment of the present invention, M 2 is Al and Cu, and the mass of Cu is greater than the mass of Al. According to another embodiment of the present invention, M 2 is Cu and Ga, and the mass of Cu is greater than the mass of Ga. According to another embodiment of the present invention, M 2 are Cu and Mg, and the mass of Cu is greater than the mass of Mg.
[0041] The grain boundary diffusion material of the present invention does not contain Fe, Co, Sn and Ti.
[0042] In some film forming processes (such as spraying), the amount of elements in the grain boundary diffusion material is the same as the element content in the rare earth alloy film formed therefrom. In other film forming processes (such as magnetron sputtering), the amount of elements in the grain boundary diffusion material (such as the amount of target material) is different from the element content in the rare earth alloy film formed therefrom.
[0043] The rare earth alloy film formed by the present invention has the following composition: x M 1 y M 2 z , wherein R is selected from at least one of Pr, Nd, Dy and Tb, and must contain a heavy rare earth element; M 1 At least one selected from Zr, Hf, Ta and Nb; M 2 Two selected from Al, Cu, Ga and Mg, and must contain Cu; x is the weight percentage of R element, y is the weight percentage of M 1 The weight fraction of the element, z is M 2 The weight percentage of the elements, and the Cu content is greater than z / 2.
[0044] Based on 100 parts by weight of the rare earth alloy film, x is 60 to 75 parts by weight, preferably 61 to 75 parts by weight, and more preferably 61 to 72.5 parts by weight; y is 3.5 to 15 parts by weight, preferably 4.5 to 15 parts by weight, and more preferably 4.8 to 14 parts by weight; z is 10 to 36.5 parts by weight, preferably 20 to 35 parts by weight, and more preferably 22.9 to 32.5 parts by weight, and the Cu content is greater than z / 2.
[0045] In the present invention, R, M 1 and M 2 The metal elements are evenly dispersed in the rare earth alloy film. Such a rare earth alloy film is conducive to better improving the coercivity of the magnet after grain boundary diffusion, with a greater increase in coercivity, a smaller rate of remanence decrease, and a higher utilization rate of heavy rare earth.
[0046] According to a specific embodiment of the present invention, the rare earth alloy film formed by the present invention has the following composition: Tb 61 Zr 14 Cu 21.3 Al 3.7 According to another specific embodiment of the present invention, the rare earth alloy film formed by the present invention has the following composition: Dy 62.5 Ta 5.4 Cu 18.3 Ga 13.8According to another specific embodiment of the present invention, the rare earth alloy film formed by the present invention has the following composition: Pr 53.8 Tb 18.5 Zr 2.2 Nb 2.6 Cu 20.6 Mg 2.3 .
[0047] The present invention believes that the use of M 1 Metals are beneficial to increase the melting point of rare earth alloys and reduce the melting point difference with the grain boundary neodymium-rich phase, so that when the temperature rises, the grain boundary phase also melts synchronously when the diffusion source melts, achieving rapid liquid-liquid diffusion. 1 Metals are conducive to preferentially reacting with impurity elements in the furnace atmosphere, diffusion materials, magnet surface and other areas during the heating process to form a phase with low activity and high melting point, thereby preventing the diffusion source from being further contaminated. 1 After the metal enters the grain boundary phase, it reacts with impurity elements such as C, N, O, and Si to eliminate the adverse effects of impurity elements on the diffusion effect of heavy rare earth elements, forming high melting point compounds to strengthen the mechanical properties of magnets. High melting point substances increase the resistance to electron transmission, increase the resistivity of magnets, and reduce eddy current losses. High melting point substances inhibit grain boundary migration during heat treatment and avoid the deterioration of magnetic properties.
[0048] The present invention adopts a specific ratio of R, M 1 and M 2 The formed rare earth alloy film can significantly improve the coercive force of the magnet while maintaining a relatively high remanence.
[0049] <Diffused magnet and preparation method>
[0050] The present invention also provides a method for preparing a diffusion magnet, comprising the following steps: (1) a pretreatment step; (2) a film forming step; and (3) a heat treatment step (ie, a grain boundary diffusion step). Detailed description is given below.
[0051] Preprocessing steps
[0052] The surface of the sintered NdFeB magnet is pretreated to remove surface contaminants, thereby obtaining a pretreated sintered NdFeB magnet, which is conducive to the formation of a film of grain boundary diffusion material on the surface of the sintered NdFeB magnet and is conducive to subsequent grain boundary diffusion.
[0053] In the present invention, the thickness of the sintered NdFeB magnet is less than or equal to 10 mm. The thickness direction is the C-axis orientation direction. According to one embodiment of the present invention, the sintered NdFeB magnet is cylindrical.
[0054] The sintered NdFeB magnet of the present invention is made of RE2Fe 14Sintered permanent magnet with B-type compound as the main phase. RE is rare earth element, including light rare earth element and heavy rare earth element. Light rare earth elements are lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm) and europium (Eu). Heavy rare earth elements are gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu) and yttrium (Y).
[0055] According to one embodiment of the present invention, RE is selected from at least one element of light rare earth elements and must contain Nd. The sintered NdFeB magnet of the present invention may contain or not contain heavy rare earth elements. In certain embodiments, the sintered NdFeB magnet of the present invention does not contain heavy rare earth elements.
[0056] The RE in the present invention can be selected from at least one of La, Ce, Nd, Pr, and Sm. According to a specific embodiment of the present invention, RE is selected from at least one element of Pr and Nd, and must contain Nd. According to a preferred embodiment of the present invention, RE is Nd and Pr. In the present invention, B is boron.
[0057] In the present invention, the sintered NdFeB magnet may contain M, where M is selected from one or more of Cu, Co, Al, Ga and Zr.
[0058] In certain specific embodiments, the sintered NdFeB magnet has the following specific composition: RE, Fe, B, Cu, Co, Al, Ga, Zr and other inevitable impurities. Based on all the elements of the sintered NdFeB magnet, RE is PrNd (the mass ratio of the two is 1:3), and the content of RE is 29.0-33.0wt%, preferably 30.0-32.0wt%. Based on all the elements of the sintered NdFeB magnet, the content of Cu is 0.10-0.60wt%, preferably 0.1-0.3wt%. The content of Co is 0.1-1.5wt%, preferably 0.2-1.0wt%. The content of Al is 0.1-1.2wt%, preferably 0.2-1.0%. Based on all the elements of the sintered NdFeB magnet, the content of B is 0.88-0.95wt%, preferably 0.89-0.93wt%. Based on all elements of the sintered NdFeB magnet, the content of Ga is 0.05-0.6wt%, preferably 0.1-0.5wt%. Based on all elements of the sintered NdFeB magnet, the content of Zr is 0.05-0.55wt%, preferably 0.1-0.50wt%. Fe is the balance.
[0059] In the present invention, the pretreatment comprises the following steps: using sandblasting to remove pollutants on the surface of the sintered NdFeB magnet, and then ultrasonically cleaning with an organic solvent to obtain a pretreated sintered NdFeB magnet. The pressure of the sandblasting can be 0.2-0.5 MPa, preferably 0.25-0.4 MPa, and more preferably 0.3-0.4 MPa. The pollutants on the surface of the sintered NdFeB magnet are mainly oil stains. The organic solvent can be selected from one of methanol, ethanol, isopropanol, and acetone, for example, ethanol.
[0060] Film forming steps
[0061] The grain boundary diffusion material as described above is used to form a rare earth alloy film on two opposite surfaces of the pretreated sintered NdFeB magnet perpendicular to the C-axis orientation direction through a film forming process to obtain a coated magnet, which is beneficial to improving the coercive force of the magnet and saving the amount of heavy rare earth.
[0062] In the present invention, the film forming process is selected from one of spraying, screen printing, laser cladding, brazing, evaporation coating and magnetron sputtering, preferably magnetron sputtering.
[0063] According to a specific embodiment of the present invention, the grain boundary diffusion material is used as the target material for co-sputtering. During co-sputtering, multiple target positions are focused on the workpiece disk area where the sample (i.e., the pretreated sintered NdFeB magnet) is located, and the workpiece disk rotates around the axis to achieve uniform composition and thickness of the rare earth alloy film obtained by sputtering.
[0064] In the present invention, the thickness of the formed rare earth alloy film may be less than 60 μm, preferably 15 to 35 μm, more preferably 20 to 35 μm, and even more preferably 25 to 32 μm.
[0065] Heat treatment steps
[0066] The obtained coated magnet is subjected to vacuum heat treatment to obtain a diffused magnet. Specifically, the coated magnet is placed in a vacuum heat treatment furnace, and the temperature is raised to 700-850°C under the condition of a vacuum degree of less than 5Pa, and the temperature is kept at this temperature for 0.5-5 hours; then the temperature is continued to be raised to 850-950°C, and the temperature is kept at this temperature for 3-8 hours, and after the insulation is completed, it is cooled to room temperature; then the temperature is raised to 400-658°C, and the temperature is kept at this temperature for 1-3 hours, and after the insulation is completed, it is cooled to room temperature to obtain a diffused magnet. This is conducive to obtaining a rare earth permanent magnet with stable performance.
[0067] In the present invention, the vacuum heat treatment is performed in a vacuum heat treatment furnace. The vacuum degree during the heat treatment is less than or equal to 5 Pa, preferably less than or equal to 1 Pa, and more preferably less than or equal to 0.1 Pa.
[0068] In the present invention, vacuum heat treatment includes primary heat treatment, secondary heat treatment and tertiary heat treatment. The primary heat treatment includes: placing the coated magnet in a vacuum heat treatment furnace, heating it to 600-850°C under the condition of a vacuum degree of less than 50Pa, and keeping it at this temperature for 0.5-5h. The temperature of the primary heat treatment can be 600-850°C, preferably 620-800°C, and more preferably 625-750°C. The time of the primary heat treatment can be 0.5-5h, preferably 1-3h, and more preferably 1-2.5h.
[0069] The temperature of the secondary heat treatment may be 850 to 950° C., preferably 860 to 950° C., more preferably 870 to 930° C. The time of the secondary heat treatment may be 3 to 8 hours, preferably 5 to 8 hours, more preferably 6 to 8 hours.
[0070] After the secondary heat treatment, the mixture is quickly cooled to room temperature.
[0071] The temperature of the tertiary heat treatment may be 400 to 658° C., preferably 450 to 625° C., more preferably 480 to 560° C. The time of the tertiary heat treatment may be 1 to 3 hours, preferably 1.5 to 3 hours, more preferably 2 to 3 hours.
[0072] After the third-stage heat treatment is completed, it is quickly cooled to room temperature to obtain a diffusion magnet.
[0073] During the heating process of the primary heat treatment, the secondary heat treatment and the tertiary heat treatment, the heating rate is preferably controlled. The heating rate of the primary heat treatment and the secondary heat treatment can be 2.5 to 5.5°C / min, preferably 3 to 4.5°C / min. The heating rate of the tertiary heat treatment can be 3.5 to 7.5°C / min, preferably 5 to 7°C / min.
[0074] The present invention provides a diffused magnet obtained by the preparation method as described above. The coercivity of the diffused magnet obtained by the present invention is significantly improved, the coercivity improvement is greater than or equal to 11.8 kOe, and can even reach 12.35 kOe, while the remanence decrease rate is less than or equal to 1.3%, preferably less than or equal to 1.15%, and the remanence decrease can be 0.28%. In addition, in the present invention, the utilization rate of heavy rare earth is relatively high.
[0075] <Test Method>
[0076] Determination of magnetic properties: Use BH magnetometer to measure the magnetic properties of sintered NdFeB magnets and diffused magnets at room temperature, including room temperature remanence Br and room temperature coercivity Hcj.
[0077] The calculation method of heavy rare earth utilization rate is as follows:
[0078] Heavy rare earth utilization rate = △Hcj / (((M0-M1) / M1)×p%), unit kOe / wt%, where △Hcj is the difference between the coercive force of the diffused magnet and the coercive force of the sintered NdFeB magnet; M1 is the weight of the original magnet before coating; M0 is the weight of the sintered NdFeB magnet after coating, which is the same as the weight of the magnet after diffusion; p% is the heavy rare earth content in the rare earth alloy film obtained in the coated magnet.
[0079] Example 1
[0080] A cylindrical N50 sintered NdFeB magnet with a diameter of 10 mm and a thickness of 5 mm is provided. The sintered NdFeB magnet is subjected to a sandblasting process to remove pollutants on the surface thereof, the sandblasting pressure being 0.3 MPa, and anhydrous ethanol is used for ultrasonic cleaning after the sandblasting to obtain a pretreated sintered NdFeB magnet.
[0081] A grain boundary diffusion material is provided as a target for magnetron sputtering. The grain boundary diffusion material includes metal Tb with a purity of 99.5%, CuAl alloy (the weight ratio of Cu to Al is 5:1) and metal Zr. The three are co-sputtered to form three targets. The grain boundary diffusion material is used as a co-sputtering target and co-sputtered on the upper surface and the lower surface (i.e., the two surfaces perpendicular to the thickness direction) of a cylindrical magnet. The rare earth alloy film sputtered on the upper surface is 32 μm, and the rare earth alloy film sputtered on the lower surface is 32 μm, thereby obtaining a coated magnet. Among them, based on 100 parts by weight of the rare earth alloy film sputtered on one surface, Tb is 61 parts by weight, Cu is 21.3 parts by weight, Al is 3.7 parts by weight, and Zr is 14 parts by weight.
[0082] The coated magnet was placed in a vacuum heat treatment furnace for vacuum heat treatment, as follows: when the vacuum degree of the vacuum heat treatment furnace was 3Pa, electric heating was started, the heating rate was 3℃ / min, the temperature was raised to 675℃, and the temperature was kept at this temperature for 60min; then the temperature was continued to be raised to 905℃, and the temperature was kept at 905℃ for 325min, and then cooled to room temperature after the insulation; then the temperature was heated again, the heating rate was 5℃ / min, the temperature was raised to 505℃, and the temperature was kept at this temperature for 120min, and then cooled to room temperature after the insulation was completed, and a diffused magnet was obtained. Some process parameters are shown in Table 1, and performance tests are shown in Table 2.
[0083] Example 2
[0084] A cylindrical N50 sintered NdFeB magnet with a diameter of 10 mm and a thickness of 5 mm is provided. The sintered NdFeB magnet is subjected to a sandblasting process to remove pollutants on the surface thereof, the sandblasting pressure being 0.3 MPa, and anhydrous ethanol is used for ultrasonic cleaning after the sandblasting to obtain a pretreated sintered NdFeB magnet.
[0085] A grain boundary diffusion material is provided as a target for magnetron sputtering. The grain boundary diffusion material includes metal Dy with a purity of 99.5%, a CuGa alloy (the weight ratio of Cu and Ga is 1.3:1) and a metal Ta target. The three are co-sputtered to form three targets. The grain boundary diffusion material is used as a co-sputtering target and co-sputtered on the upper surface and the lower surface (i.e., the two surfaces perpendicular to the thickness direction) of a cylindrical magnet. The rare earth alloy film sputtered on the upper surface is 31.5 μm, and the rare earth alloy film sputtered on the lower surface is 31.5 μm, thereby obtaining a coated magnet. Among them, taking the rare earth alloy film sputtered on one surface as 100 parts by weight as a basis, Dy is 62.5 parts by weight, Cu is 18.3 parts by weight, Ga is 13.8 parts by weight, and Ta is 5.4 parts by weight.
[0086] The coated magnet was placed in a vacuum heat treatment furnace for vacuum heat treatment, as follows: when the vacuum degree of the vacuum heat treatment furnace was 3Pa, electric heating was started, the heating rate was 3℃ / min, the temperature was raised to 685℃, and the temperature was kept at this temperature for 90min; then the temperature was continued to be raised to 930℃, and the temperature was kept at 930℃ for 480min, and then cooled to room temperature after the insulation; then the temperature was heated again, the heating rate was 5℃ / min, the temperature was raised to 480℃, and the temperature was kept at this temperature for 120min, and then cooled to room temperature after the insulation was completed, and a diffused magnet was obtained. Some process parameters are shown in Table 1, and performance tests are shown in Table 2.
[0087] Example 3
[0088] A cylindrical 40SH sintered NdFeB magnet with a diameter of 10 mm and a thickness of 5 mm is provided. The sintered NdFeB magnet is subjected to a sandblasting process to remove pollutants on the surface thereof, the sandblasting pressure being 0.3 MPa, and then ultrasonically cleaned with anhydrous ethanol to obtain a pretreated sintered NdFeB magnet.
[0089] A grain boundary diffusion material is provided as a co-sputtering target, and the grain boundary diffusion material includes a PrTb alloy (the weight ratio of Pr and Tb is 3:1) with a purity of 99.5%, a CuMg alloy (the weight ratio of Cu and Mg is 8:1) and a ZrNb alloy (the weight ratio of Zr and Nb is 1.25:1), and the three are three targets when co-sputtered. The grain boundary diffusion material is used as a co-sputtering target and co-sputtered on the upper surface and the lower surface (i.e., the two surfaces perpendicular to the thickness direction) of a cylindrical magnet, and the rare earth alloy film sputtered on the upper surface is 29.8μm, and the rare earth alloy film sputtered on the lower surface is 29.8μm, so as to obtain a coated magnet. Among them, taking the rare earth alloy film sputtered on one surface as 100 parts by weight as a benchmark, Pr is 53.8 parts by weight, Tb is 18.5 parts by weight, Cu is 20.6 parts by weight, Mg is 2.3 parts by weight, Zr is 2.2 parts by weight, and Nb is 2.6 parts by weight.
[0090] The coated magnet was placed in a vacuum heat treatment furnace for vacuum heat treatment, as follows: when the vacuum degree of the vacuum heat treatment furnace was 5Pa, electric heating was started, the heating rate was 3℃ / min, the temperature was raised to 728℃, and the temperature was kept at this temperature for 120min; then the temperature was continued to be raised to 870℃, and the temperature was kept at 870℃ for 420min, and then cooled to room temperature after the insulation; then the temperature was heated again, the heating rate was 5℃ / min, the temperature was raised to 556℃, and the temperature was kept at this temperature for 95min, and then cooled to room temperature after the insulation was completed, and a diffused magnet was obtained. Some process parameters are shown in Table 1, and performance tests are shown in Table 2.
[0091] Table 1
[0092]
[0093] Note: The weight parts in Table 1 are based on 100 weight parts of the rare earth alloy film on one surface.
[0094] Table 2
[0095]
[0096] Note: Examples 1 and 3 are Tb alloy diffusion sources, while Example 2 is Dy alloy diffusion source. There is a significant difference in the utilization rate of heavy rare earths, which is determined by the characteristics of Tb and Dy elements.
[0097] From the comparison of the performance results of Examples 1 and 2 with the N50 sintered NdFeB magnet, and from the comparison of the performance results of Example 3 with the 40SH sintered NdFeB magnet, it can be seen that the diffused magnet obtained by co-sputtering a specific grain boundary diffusion material and vacuum heat treatment in the present invention has a very small decrease in remanence (the remanence decrease rate of Example 1 is 0.98%, the remanence decrease rate of Example 2 is 0.28%, and the remanence decrease rate of Example 3 is 1.3%), and the coercive force is greatly improved under the industrial requirement of a remanence decrease of less than 3%.
[0098] In addition, the utilization rate of heavy rare earth in the method of the present invention is high. The utilization rate of heavy rare earth Tb in the present invention reaches more than 93.00 kOe / wt%, while the utilization rate of heavy rare earth when pure Tb is diffused in grain boundaries is generally only 20-50 kOe / wt%. The utilization rate of heavy rare earth Dy in the present invention reaches 38.65 kOe / wt%, while the utilization rate of pure Dy is generally only 8-20 kOe / wt%. Therefore, the present invention can make the utilization rate of heavy rare earth higher through specific grain boundary diffusion materials.
[0099] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A grain boundary diffusion material, characterized in that: It includes R, M 1 and M 2 ; Wherein, R is selected from at least one of Pr, Nd, Dy and Tb, and must contain a heavy rare earth element; M 1 At least one selected from Zr, Hf, Ta and Nb; M 2 Two selected from Al, Cu, Ga and Mg, and must contain Cu; The grain boundary diffusion material is used to form a rare earth alloy film, and the rare earth alloy film has the following composition: x M 1 y M 2 z ,in, x is the weight fraction of R element, y is M 1 The weight fraction of the element, z is M 2 The weight percentage of the element, and the content of Cu is greater than z / 2; Based on 100 parts by weight of the rare earth alloy film, x is 60 to 75 parts by weight, y is 3.5 to 15 parts by weight, and z is 10 to 36.5 parts by weight.
2. The grain boundary diffusion material according to claim 1, characterized in that R must contain Dy or Tb; M 1 At least one selected from Zr, Ta and Nb.
3. A rare earth alloy film, characterized in that: It has the following composition: R x M 1 y M 2 z , wherein R is selected from at least one of Pr, Nd, Dy and Tb, and must contain a heavy rare earth element; M 1 At least one selected from Zr, Hf, Ta and Nb; M 2 Two selected from Al, Cu, Ga and Mg, and must contain Cu; x is the weight percentage of R element, y is the weight percentage of M 1 The weight fraction of the element, z is M 2 The weight percentage of the element, and the content of Cu is greater than z / 2; Based on 100 parts by weight of the rare earth alloy film, x is 60 to 75 parts by weight, y is 3.5 to 15 parts by weight, and z is 10 to 36.5 parts by weight.
4. A method for preparing a diffusion magnet using the grain boundary diffusion material according to claim 1, characterized in that: The following steps are involved: (1) pre-treating the surface of the sintered NdFeB magnet to remove pollutants on the surface, thereby obtaining a pre-treated sintered NdFeB magnet; (2) forming the rare earth alloy thin film on two opposite surfaces of the pretreated sintered NdFeB magnet perpendicular to the C-axis orientation direction through a film forming process to obtain a coated magnet; (3) subjecting the obtained coated magnet to vacuum heat treatment to obtain a diffused magnet; Wherein, the rare earth alloy film formed on one surface of the pretreated sintered NdFeB magnet has a thickness of less than 60 μm.
5. The method according to claim 4, characterized in that The sintered NdFeB magnet is made of RE2Fe 14 The B-type compound is the main phase, in which RE is a rare earth element.
6. The method according to claim 4, characterized in that The pretreatment comprises the following steps: using sandblasting to remove pollutants on the surface of the sintered NdFeB magnet, and then using an organic solvent to perform ultrasonic cleaning to obtain the pretreated sintered NdFeB magnet.
7. The method according to claim 4, characterized in that The film forming process is selected from one of spraying, screen printing, laser cladding, brazing, evaporation coating and magnetron sputtering.
8. The method according to claim 4, characterized in that The rare earth alloy film formed on one surface of the pretreated sintered NdFeB magnet has a thickness of 15 to 35 μm.
9. The method according to claim 4, characterized in that The vacuum heat treatment comprises the following steps: The coated magnet is placed in a vacuum heat treatment furnace, and under the condition of a vacuum degree of less than or equal to 5Pa, the temperature is raised to 600-850°C, and kept at this temperature for 0.5-5h; then the temperature is continued to be raised to 850-950°C, and kept at this temperature for 3-8h. After the insulation is completed, it is cooled to room temperature; then the temperature is raised to 400-658°C, and kept at this temperature for 1-5h. After the insulation is completed, it is cooled to room temperature to obtain a diffused magnet.
10. A diffusion magnet, characterized in that: It is prepared according to the method according to any one of claims 4 to 9.
Citation Information
Patent Citations
Grain boundary diffusion material, rare earth permanent magnet material and preparation method therefor
CN105529123A
Preparation method of high-coercivity sintered neodymium-iron-boron magnet
CN111916284A
Method for preparing high-performance neodymium iron boron permanent magnet material by improving grain boundary diffusion
CN115116734A
Grain boundary diffusion source and preparation method of high-performance and high-abundance rare earth magnet
CN117038313A
Cited By
Method for recovering grain boundary diffusion neodymium-iron-boron magnet
CN119870480A
